LEGAL ANALYSIS OF THE SUSTAINABLE DEVELOPMENT OF INDONESIA’S FOOD ESTATE PROGRAM AND ITS IMPACT ON FARMERS’ WELFARE - Suyanto Suyanto; Dwi Wachidiyah Ningsih; Prihatin Effendi (EQUALEGUM International Law Journal, 2026)
Background. Food security is crucial for countries facing climate change, population growth, and supply chain issues. Indonesia's Food Estate Program seeks to improve food security and agricultural productivity while reducing food imports. However, it has raised concerns related to its sustainability and effects on farmers' welfare. This study aimed to analyze the legal sustainability of the Food Estate Program and evaluate its implications for farmers’ welfare from the perspective of agricultural law, environmental law, and sustainable development principles. Research Methods. Normative juridical research design, the statutory approach analyzes key legal documents, including Indonesia's 1945 Constitution and several laws regarding food, farmer protection, and agricultural land sustainability. The conceptual approach applies theories related to sustainable development and agrarian justice. The comparative approach assesses international standards on sustainable agriculture and food security within global development frameworks. Findings. Although the Food Estate Program is supported by a substantial regulatory framework, significant challenges remain regarding land governance, environmental protection, indigenous rights, community participation, and equitable distribution of economic benefits. Sustainable food estate development requires a transition from a production-oriented approach toward a farmer-centered legal framework emphasizing social justice, environmental sustainability, and participatory governance. Such reforms are essential to ensure that food security policies contribute not only to national food production but also to the long-term welfare of farming communities. Conclusion. Achieving sustainable development necessitates a shift to a farmer-centered legal framework that prioritizes social justice and participatory governance, ensuring food security policies enhance both national food production and the long-term welfare of farming communities.